2018
DOI: 10.1002/elsc.201800141
|View full text |Cite
|
Sign up to set email alerts
|

Low cell surface hydrophobicity is one of the key factors for high butanol tolerance of Lactic acid bacteria

Abstract: Highly butanol‐tolerant strains have always been attractive because of their potential as microbial hosts for butanol production. However, due to the amphiphilic nature of 1‐butanol as a solvent, the relationship between the cell surface hydrophobicity and butanol resistance remained ambiguous to date. In this work, the quantitatively estimated cell surface hydrophobicity of 74 Lactic acid bacteria strains were juxtaposed to their tolerance to various butanol concentrations. The obtained results revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…As a result, this shows that all three isolates in this study possessed the hydrophilic nature of the cell surface. This is supported by several studies where L. lactis, L. paracasei, L. plantarum, L. fermentum, L. casei, and L. rhamnosus were found to have hydrophilic surfaces (Bhanwar et al, 2014;Sadrani et al, 2014;Petrova et al, 2019).…”
Section: Microbial Adhesion Of Lab Isolates Towards Different Types Of Solventsmentioning
confidence: 58%
“…As a result, this shows that all three isolates in this study possessed the hydrophilic nature of the cell surface. This is supported by several studies where L. lactis, L. paracasei, L. plantarum, L. fermentum, L. casei, and L. rhamnosus were found to have hydrophilic surfaces (Bhanwar et al, 2014;Sadrani et al, 2014;Petrova et al, 2019).…”
Section: Microbial Adhesion Of Lab Isolates Towards Different Types Of Solventsmentioning
confidence: 58%
“…Butanol stress alters first of all the content and structure of the cell envelope. The results from the differential gene expression showed that L. plantarum most probably increases the production of exopolysaccharides (EPS) to build up a physical barrier between the solvent and the cell wall, as well as to increase the cell envelope hydrophilicity, which has been shown to enhance butanol resistance [ 34 ]. Six DEGs with FC between +2.0 and +3.4 responsible for EPS synthesis are overexpressed only in Ym1: wzx gene encoding oligosaccharide flippase (lp_2099), wzy for polysaccharide polymerase (lp_2101), and three genes encoding different ‘polysaccharide biosynthesis’ proteins (lp_2108, lp_1221, and lp_1225), well-characterized as part of the cps gene clusters in L. plantarum WCFS1 [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…L. plantarum is a species that participates in lactic acid fermentation of numerous beverages and foods, including wine, yoghurt, boza, sourdough, sauerkraut, and sausages [ 32 , 33 , 34 ], and is typically resistant to environmental stress caused by acidic pH, extremes in temperature, osmotic pressure, oxygen, starvation, and high alcohol concentrations [ 35 , 36 ]. Selected strains of L. plantarum can grow at butanol concentrations up to 3–4% ( v / v ) [ 34 , 37 ]. Despite these promising data, the reasons for the butanol resistance of L. plantarum have been studied very little on a genetic level and remain elusive [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting intestinal chyme was incubated (37 • C, pH 7) for 2 h. At the end of each stage, aliquots of each sample (1 mL) were diluted in 9 mL of sterile peptone water (0.2%, w/v) and placed in a stomacher for 30 s. The bacterial count was obtained by serially diluting the Foods 2021, 10, 2677 5 of 20 suspensions, followed by incubation in MRS agar plates at 37 • C for 48 h. CT content was determined via UV-Vis spectrophotometry at wavelength 281 nm following the method described in Section 2.5.2. The surface hydrophobicity of the free and encapsulated bacteria cells was determined using the microbial adhesion to hydrocarbons method according to Petrova et al [28], with some modifications. The microparticles were mixed with a sodium phosphate buffer (0.4 M) solution and stirred to allow the release of bacteria cells.…”
Section: In Vitro Stability and Cells Surface Hydrophobicity 2111 In Vitro Stability Of The Encapsulated Probioticsmentioning
confidence: 99%